Assessing Impacts of Math in Focus, a "Singapore Math" Program. Issue 4 (1st October 2016) - Jaciw, Andrew P.; Hegseth, Whitney Michelle; Lin, Li; Toby, Megan; Newman, Denis; Ma, Boya; Zacamy, Jenna
ABSTRACT: This study investigates, through a cluster randomized trial, the impact of Math in Focus, a core mathematics program modeled after instructional approaches used in Singapore, on third- through fifth-grade students' achievement in mathematics. The program is currently being used in more than 400 school districts in the United States. The program focuses on coherence of coverage of materials across grades, use of the Concrete to Pictorial to Abstract approach to instruction, and covering fewer topics, but addressing them more thoroughly. Twenty-two grade-level teams across 12 schools were randomized to the program or business as usual. Measures included indicators of fidelity to treatment, and student mathematics learning. Impacts on mathematics achievement ranged from .11 to .15 standard deviation units. No differences in impact were observed depending on level of incoming achievement, minority status, or grade level. Impact of Math in Focus did not vary across the procedures and problem-solving subscales. Discussion of findings includes the nature of the counterfactual, and possible future direction of impact studies that may focus in greater depth on the critical features of inquiry instruction unique to Math in Focus.